Clinical outcomes of endoscopic resection for nonampullary duodenal high-grade dysplasia and intramucosal carcinoma - Maruoka, D.; Arai, M.; Kishimoto, T.; Matsumura, T.; Inoue, M.; Nakagawa, T.; Watanabe, Y.; Katsuno, T.; Tsuyuguchi, T.; Imazeki, F.; Yokosuka, O. (Endoscopy, 2013)
This study retrospectively analyzed the clinical outcomes of endoscopic resection of 26 sporadic (i. e., not associated with polyposis syndrome) nonampullary duodenal lesions representing high-grade dysplasia or intramucosal carcinoma (duodenal HGD/IMC) in 23 patients. No severe complications such as perforation were observed, but three cases of delayed bleeding were seen. The use of endoscopic clips significantly decreased the delayed bleeding rate (0 /19, 0 %) compared with cases in which clips were not used (3 /7, 42.9 %; P = 0.013, χ2 test). Eighteen lesions (69.2 %) were removed by en bloc resection. The follow-up period after resection was 25.5 ± 23.3 months. Two lesions (7.7 %) that recurred locally were detected at the first surveillance endoscopy 3 months after resection. These lesions were 22 and 15 mm in size respectively and were resected piecemeal. Endoscopic resection is an effective and safe procedure for treating duodenal HGD/IMC. En bloc resection and prophylactic clip usage are encouraged.